Trends in nationwide incidence of pediatric type 1 diabetes in Montenegro during the last 30 years - Raicevic, Maja; Samardzic, Mira; Soldatovic, Ivan; Curovic Popovic, Natasa; Vukovic, Rade (Frontiers in Endocrinology, 2022)
Significant and unexplained variations of type 1 diabetes mellitus (T1D) incidence through years were observed all around the world. The update on this disorder`s incidence is crucial for adequate healthcare resource planning and monitoring of the disease. The aim of this study was to give the update on the current incidence of pediatric T1D in Montenegro as well as to analyze incidence changes over time and how the exposure to different factors might have affected it. This retrospective cohort study included a total of 582 patients younger than 15 years, who were newly diagnosed with T1D during the past 30 years. The average age at diagnosis was 8.4±3.91 years. Mean annual incidence of T1D in Montenegro population during the whole study period of 30 years was 15.16/100000 person years. Slightly higher incidence rates were observed in males, compared to females and the incidence increased with age, with the highest incidence in the 10-14 age group. If the model is observed as one without jointpoints, the APC for total population is 3.1 (1.8-4.4), for males 3.8 (2.1-5.5) and for females 2.1 (0.6-3.5). In 2020, the first year of COVID19 pandemic, in comparison to 2019, the incidence rate increased from 19.7/100000 to 21.5/100000, with the highest increase in age group 5-9 year. This is the first nation-wide report on 30 years period of T1D incidence trend in Montenegro. It suggests that T1D incidence among Montenegrin children is rising again, and that there is a short- term influence of COVID19 on new onset T1D.